The Functional Characteristics O Karakteristik Fungsional Sereal Flake Tepung Garut Substitusi Tepung Shorgum Sebagai Pangan Fungsional Pre-Biotik Rendah Gluten: Functional Characteristics of Arrowroot Flour Cereal Flakes Substituted with Sorghum Flour as a Low-Gluten Prebiotic Functional Food - Khusnul Khotimah; Rahadina Praba Melati; Nofia Liza Romadhoni (Amerta Nutrition, 2026)
Background: Cereal flakes are ready-to-eat breakfast products commonly made from wheat flour, which may be unsuitable for individuals with gluten intolerance. The use of local non-wheat flours, such as arrowroot and sorghum flour, offers an alternative for producing low-gluten cereal flakes with potential nutritional benefits. Objectives: This study aimed to determine the best formulation of low-gluten cereal flakes based on chemical characteristics and sensory acceptability. Methods: A completely randomized design was used with four flour formulations: F1 (30%:70%:0%), F2 (30%:60%:10%), F3 (30%:50%:20%), and F4 (30%:40%:30%). Each treatment was replicated three times using 150 g of flour mixture. Chemical analyses included moisture, ash, fat, protein, carbohydrate, crude fiber, and tannin contents. Sensory evaluation was conducted by 35 panelists using a hedonic test for color, aroma, taste, texture, and overall acceptability. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test at a 5% significance level. Results: Formula F2 had the lowest moisture content (1.11±0.48%), the highest ash content (1.51±0.17%), and the highest crude fiber content (0.33±0.01%). Protein content was low in all formulations, with the lowest value observed in F2 (2.82±0.12%). Carbohydrate content ranged from 65.89% to 74.27% and was not significantly different among treatments. Formula F4 showed the highest tannin content (82.55±0.19%). Sensory evaluation showed that F2 had the highest overall acceptability score (4.51±0.70) and differed significantly from other formulations. Conclusions: Formula F2 (30%:60%:10%) was the best formulation, providing a favorable balance between chemical characteristics and sensory acceptability, and met the SNI 01-2886-2000 standard.